The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/ehjcvp/pvaa062
|View full text |Cite
|
Sign up to set email alerts
|

Association between renin–angiotensin system inhibitors and COVID-19 complications

Abstract: Aims To describe the characteristics of patients hospitalized with COVID-19 (including their long-term at-home medication use), and compare them with regard to the course of the disease. To assess the association between renin–angiotensin system inhibitors (RASIs) and disease progression and critical outcomes. Methods and results All consecutive hospitalized patients with laboratory-confirmed COVID-19 in a university hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…We reported a negative impact of ACE-I and ARB use among hospitalized Korean patients. Liabeuf et al described the association of RAS blockade use with a higher risk of severe COVID-19 in 268 hospitalized patients, which is consistent with our results 21 . The difference of these studies compared with the previous reports is that all confounding factors such as body mass index, blood pressure, and various laboratory data were identi ed in severe hospitalized patients with COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…We reported a negative impact of ACE-I and ARB use among hospitalized Korean patients. Liabeuf et al described the association of RAS blockade use with a higher risk of severe COVID-19 in 268 hospitalized patients, which is consistent with our results 21 . The difference of these studies compared with the previous reports is that all confounding factors such as body mass index, blood pressure, and various laboratory data were identi ed in severe hospitalized patients with COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…The characteristics of the shortlisted studies are summarized in Table 1. Among shortlisted studies, 23 studies were from China , nine studies were from Italy [64][65][66][67][68][69][70][71][72], ten studies were from the United States [83][84][85][86][87][88][89][90][91][92], four studies were from South Korea [75][76][77][78], three studies were from France [60][61][62], two studies were from Spain [79,80], one study each was from Belgium [35], Denmark [59], Hong Kong [63], Kuwait [73], Singapore [74], Turkey [81], and the United Kingdom [82]; and one study included data from 38 countries [93]. There were 24 studies that included hypertensive patients exclusively (100%) [36, 38, 39, 43-45, 47, 48, 50-52, 54, 56, 58, 66, 71, 72, 75, 78, 81, 87-89, 91].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The comparison of mortality and clinical severity outcomes between ACEI/ARB users and non-ACEI/ARB users with COVID-19 is summarized in [35,40,52,56,59,61,63,66,74,75,78,80,84,89,90,92] provided adjusted estimates for severe/critical disease with the use of an ACEI/ ARB relative to the non-use of an ACEI/ARB. , it was unclear whether the entire included cohort of patients was followed until discharge/death.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Certainly, the contradictory ndings reported in different populations with regards to the severity of COVID-19 may suggest population differences at play [20][21][22][23] [47][48][49]. For example, in a study by Mehta et al in the United States, showed no signi cant association between ACEI/ARB use and mortality, while it reported potential harmful effects with ACEI/ARB use including higher hospital and ICU admissions [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that exposing patients to ACEI/ARB may increase the expression of ACE2 by a negative feedback mechanism, thus facilitating the binding process of coronavirus to epithelial cells of the kidney, intestine, lung, and blood vessels [15] and increasing the risk of developing severe and fatal COVID-19 disease [16][17][18]. Clinical research evidence to date has been equivocal, especially in terms of identifying differentiating factors that may mediate the ACEI/ARB and COVID-19 severity relationship [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%